Green manure incorporation timing for organically grown broccoli - Diniz, Ellen Rúbia; Santos, Ricardo Henrique Silva; Urquiaga, Segundo Sacramento; Peternelli, Luiz Alexandre; Barrella, Tatiana Pires; Freitas, Gilberto Bernardo de (Pesquisa Agropecuária Brasileira, 2007)
The objective of this work was to determine the effect of incorporation timing of the velvet bean (Stizolobium cinereum) (GM) on both organic broccoli yield and N status. Mineral N content in the soil, biologically fixed N recovery by broccoli, GM biomass decomposition and N release kinetics were also determined. Plots were fertilized with 12 Mg ha-1 of organic compost and received GM either at 0, 15, 30 or 45 days after transplant. Other treatments were compost (12 or 25 Mg ha-1), GM, mineral fertilizers and control (no fertilizer). The data were collected in four completely randomized blocks. GM decomposition increased mineral N content in soil as rapidly as mineral fertilizer or the supply of 25 Mg ha-1 of compost. The N half-life in GM (24 days) is smaller than the mass half-life (35 days) and the biological fixation contributed with 23.6% of N present in the aboveground biomass of broccoli. The result suggests a higher synchrony between the crop relative growth rate and N release from the GM when incorporated at crop early growth stage. The incorporation of GM until 15 days after transplanting replaces 50% of the highest compost dose, without yield loss.

O objetivo deste trabalho foi determinar o efeito do momento da incorporação de mucuna-cinza (Stizolobium cinereum) (AV) sobre a produtividade e o teor de N do brócolis orgânico. Foram determinados o teor de N mineral no solo, a recuperação de N fixado biologicamente no brócolis e a cinética de decomposição da massa e liberação de N do AV. As parcelas foram fertilizadas com 12 Mg ha-1 de composto orgânico e receberam AV aos 0, 15, 30 e 45 dias depois do transplante. Outros tratamentos foram: composto orgânico (12 ou 25 Mg ha-1), AV, fertilizante mineral e testemunha. A decomposição do AV aumentou o teor de N mineral no solo tão rapidamente quanto o fertilizante mineral ou a aplicação de 25 Mg ha-1 de composto orgânico. A meia-vida de N no AV (24 dias) é menor que a meia-vida da massa (35 dias) e a fixação biológica contribuiu com 23,6% do N da parte aérea do brócolis. Os resultados sugerem maior sincronia entre a taxa de crescimento relativo da cultura e a liberação de N do AV, quando incorporado no início do cultivo. A incorporação do AV até 15 dias depois do transplante substitui 50% da dose de composto sem perda de produtividade.
Keywords: Brassica oleracea; Stizolobium cinereum; Biological nitrogen fixation; Decomposition rate; N recovery; Fixação biológica do nitrogênio; Taxa de decomposição; Recuperação de nitrogênio